PENGARUH GREEN ACCOUNTING, PERENCANAAN PAJAK, DAN MANAJEMEN ASET TERHADAP PROFITABILITAS PERUSAHAAN SMALL MIDDLE CAP DI BURSA EFEK INDONESIA - Cecilia Chelsea Kaligis; Francis M Hutabarat; Richard Friendly Simbolon (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The purpose of this study is to determine the effect of green accounting, tax planning, and asset management on the profitability of small-to-middle-cap companies listed on the Indonesia Stock Exchange. Company data was obtained from company publications in financial reports accessible on the company website and the Indonesia Stock Exchange website for 20 small-to-middle-cap companies observed from 2021 to 2024. Green accounting, tax planning, and asset management were used as independent variables, while profitability was used as the dependent variable. Data analysis used regression analysis, hypothesis testing, descriptive analysis, and classical assumption testing. The results showed that green accounting and asset management significantly influenced profitability. However, tax planning did not. Simultaneously, operational variables significantly influenced the profitability of small-to-middle-cap companies listed on the IDX.